THE IMPACT OF AI TOOLS ON EFL LEARNERS SPEAKING FLUENCY DEVELOPMENT IN EMI CONTEXTS - Toshmatov, Alimardon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
Speaking fluency is vital for students participating in EMI courses, as it enables them to effectively communicate in discussions, give presentations, and engage in seminars and tutorials․ However, EFL students typically lack opportunities for sustained speaking practice, face heightened anxiety levels, and receive inadequate individual feedback․ AI tools such as conversational chatbots, speech recognition, and AI-based feedback tools can be used to address these challenges․ This quasi-experimental study explored the impact of speaking practice with AI tools on EMI students' oral ‌fluency development after a 4-week intervention․ Participants (60 undergraduate EMI students with a B1-B2 level of expertise) were assigned to a control group and an experimental group․ The experimental group experienced an intervention where students had to perform role-plays with ChatGPT, use speech-to-text applications, and incorporate AI-generated feedback, whereas the control group engaged in customary speaking activities․ Fluency measures (speech rate in words per minute, pauses per minute, and mean length of utterance) were collected pre- and post-intervention․ In the experimental group, fluency statistics showed a considerably increased speech rate, decreased pause rate, and improved confidence as compared to participants in the control group․ The results indicate that AI-supported practice is an effective way to provide low-anxiety, individualized speaking practice that can help students make progress towards their speaking goals outside the classroom․ The pedagogical implications of using AI tools in blended learning EMI settings suggest that mediation by instructors is important for students' effective use of AI-assisted learning in developing their speaking skills․